2018
DOI: 10.1016/j.jmatprotec.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-mechanical recycling of rubber: Relationship between material properties and specific mechanical energy

Abstract: The studied and optimized devulcanization process is known as "High Shear Mixing" (HSM) recycling process. In the process the rubber is sheared between two metallic cones with special geometries. One cone is static as the other one rotates simultaneously and applies pressure to the material.Among the different parameters that are controlled and/or measured during the process two are highlighted for their importance: the temperature of the rubber, and the specific mechanical energy consumed during the process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…Diaz et al [ 34 ] performed thermo-mechanical reclaiming of ethylene-propylene-diene rubber in a special high shear mixer (HSM) designed as a rotor-stator system that was equipped with a cooling system dedicated independently to the rotor and stator to control rubber self-heating phenomenon. In conclusion, the authors indicated that specific mechanical energy can be used as an indicator of rubber reclaiming efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Diaz et al [ 34 ] performed thermo-mechanical reclaiming of ethylene-propylene-diene rubber in a special high shear mixer (HSM) designed as a rotor-stator system that was equipped with a cooling system dedicated independently to the rotor and stator to control rubber self-heating phenomenon. In conclusion, the authors indicated that specific mechanical energy can be used as an indicator of rubber reclaiming efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…168 As a result, the recycling of thermoset rubber tires has been developed to a greater extent, but similar to FRPs, high-energy-intensive mechanical and thermal recycling are also indicated as the most economically feasible options for this class of thermosets. 169,170 The most straightforward approach to utilize dynamic covalent linkages in cross-linked rubbers seems to be via disulfide linkages which are already present in cross-linked (natural) rubbers due to sulfur vulcanization. 171,172 By tuning of the molecular architecture and addition of CuCl 2 catalyst, healing and easy repair of these rubbers are possible, but due to the associative nature of the disulfide linkages, the reprocessing and recycling is just as complex as it is for conventional rubbers.…”
Section: Application Perspectivementioning
confidence: 99%
“…Thermo-chemical regeneration is based on applying thermal energy and mechanical mixing/ kneading, as well as adding chemical reclaiming agents to combine the advantages of both regeneration processes. However, elevated temperature might result in severe degradation of the main chain and a drop of the mechanical properties for the regenerated rubber [93,109].…”
Section: Thermo-chemical Processesmentioning
confidence: 99%